Low cost, high performance flexible asymmetric supercapacitor based on modified filter paper and an ultra-fast packaging technique. Issue 87 (5th September 2016) - Su, Haibo; Zhu, Pengli; Zhang, Leicong; Zeng, Wenjin; Zhou, Fengrui; li, Gang; Li, Tingxi; Wang, Qing; Sun, Rong; Wong, Chingping
Abstract : A low cost, high performance flexible PF–RGO//PF–RGO–PANI asymmetric supercapacitor based on modified filter paper is reported together with an ultra-fast and layer by layer packaging technique. Abstract : A flexible all-solid-state asymmetric supercapacitor (FAAS) was prepared via a low-cost method with commonly used paper fibers as the substrate and a modified polymer-based hydrogel as the electrolyte. In the designed structure of the positive electrode, a three dimensional network of stacked thin film based on paper fibers (PFs), chemically reduced graphene oxide (RGO) and the electro-polymerization of polyaniline (PANI) nanorods was prepared via an extended filtration assisted method. The fabricated PF–RGO–PANI electrodes exhibit large specific capacitance of 587 F g −1 at the current density of 0.8 A g −1 and excellent cycling stability (99.6% retention of initials specific capacitance even after 5000 cycles). PF–RGO film was introduced as the negative electrode for the designed asymmetric supercapacitor. During the preparation process of FAAS, a glutaraldehyde (GA) cross-linked PVA–H2 SO4 hydrogel was not only used as the electrolyte but also explored as a separator and external packaging material prepared by a fast layer-by-layer assembly technique within one minute. The resulted FAAS exhibits a maximum energy density and power density of 175 W h kg −1 and 9200 W kg −1 . Moreover, superior mechanical stability of the FAAS has been demonstrated by testing its bending and folding performance, which retains over 84% of its original specific capacitance even after 2000 cycles of bending and folding. The simple and low-cost preparation process of electrodes, the ultra-fast flexible supercapacitor assembling and the efficient packaging technique proposed in this study provide a good contribution to the development of FAAS for the next generation flexible energy storage devices.